Understanding the profitability, supply, and input demand of tobacco farms in Khyber Pakhtunkhwa, Pakistan - Sajjad; Zahoor Ul Haq; Javed Iqbal; Muhammad Shahzad (Economies, 2022)
Several studies investigate the various aspects of tobacco at the processing and cigarette manufacturing levels, but the profitability, supply response, and input demand of tobacco farms in Pakistan remain unknown. Our study fills this gap by examining farm-level profitability, input demand, and output supply using survey data of 140 tobacco farms by employing a profit function approach. The results show that tobacco production is not very lucrative at the farm level and farmers are responsive to changes in market prices for the inputs and output. The price of tobacco is the most important determinant of the output supply and demand for inputs, and farmers' response to increasing tobacco prices is positive but inelastic in the study area. The use of variable inputs such as fertilizers, labor, mechanical power, pesticides, and farmyard manure is important in resource allocation decisions in tobacco production. As a result, a price increase for green tobacco leaves would significantly increase the demand for farm inputs such as fertilizers, labor, mechanical power, pesticides, and farmyard manure. Tobacco production is negatively affected by the increasing input prices in the study area. Among the fixed factors, land area has a significant impact on tobacco productivity in the province. The present study is the first to quantify the farm-level input demand and output supply; therefore, based on the findings, the increasing tobacco production requires higher output prices and reasonable input prices.
Keywords: 330; input demand; Khyber Pakhtunkhwa; profitability; tobacco supply; trans-log profit function